Improvement of Bovine Split Hide Gelatin Quality by Addition of Soy Protein Isolate Using Transglutaminase Enzyme - D. Wulandari; Y. Erwanto; Y. Pranoto; Rusman Rusman; R. Yuliatmo (Faculty of Animal Science, Bogor Agricultural University, 2019)
Bovine split hide is the subcutis layer with the low percentage of collagen so that the quality of the gelatin is different from that of the gelatin from cattle’s skin. This study aims to improve the characteristics of bovine split hide gelatin combined with soy protein isolate (SPI) using transglutaminase (TGase) enzyme as a protein cross-linking agent. The study was conducted using a completely randomized design with 3 x 3 factorial pattern consisting of three levels of a mixture of bovine split hide gelatin : SPI at the ratios of 90 : 10, 80 : 20, 70 : 30, and three concentrations of transglutaminase enzyme, i.e. 10, 20, and 30 U. The results showed that treatments significantly affected viscosity, gel strength, the moisture, ash, fat, and protein content of gelatin. Electrophoresis of gelatin protein showed bands distribution between 60-190 kDa. The amino acid profile of the gelatin was similar to that of collagen with a high level of aspartate, glutamate, cysteine, and proline. Morphology of gelatin was observed by Scanning Electronic Microscope (SEM) and showed a compact distributed collagen crosslink. The combination of gelatin bovine split hide and SPI at the ratio of 90 : 10 provides the best physicochemical characteristic.